Robotic-assisted Burch operation using an alloplant for urinary incontinence: Clinical case - V. N. Pavlov; A. G. Yаshchuk; I. R. Kabirov; Z. M. Galanova; S. F. Nasyrova; Z. T. Yudina; V. R. Murzin; G. H. Murtazina (Креативная хирургия и онкология)
Introduction. Urinary incontinence is an urgent problem in urogynecology and the number of patients with this pathology is steadily increasing. The main treatment method of urinary incontinence in women includes synthetic suburethral slings. Currently, more than 200 operations for stress urinary incontinence are carried out. One of the methods of surgical treatment of this pathology implies Burch colposuspension, which has been considered the gold standard treatment of stress urinary incontinence for recent decades. Aim. This study aims to describe a clinical case of using an alloplant in a robotic-assisted Burch operation for urinary incontinence.Materials and methods. A 48-year-old patient was admitted to the BSMU Clinic in a planned manner with complaints of urinary incontinence during coughing, sneezing, and physical exertions as well as of a feeling of a foreign body in the vagina. The examination results confirmed a diagnosis of stress urinary incontinence. Comorbidities: Pelvic floor weakness. 2–3 degrees omission of the anterior vaginal wall. Cystocele. POP-Q 2. It was decided to perform a robotic-assisted Burch operation using an alloplant.Results and discussion. The postoperative period proceeded without complications. A Foley’s catheter was removed on the first day. After its removal, natural urination was restored. The stitches were removed on the fifth day. The wound healed by primary intention healing. Urine was retained well during functional tests. On the 7th and 30th days, magnetic resonance imaging (MRI) revealed no inflammatory processes at the fixation site of the allograft. The allograft was retained, its integrity was preserved, and no pathology was detected. Patient examination at a distant time after surgery (2, 4, and 12 months) revealed that the function of the bladder to hold urine was preserved.Conclusion. Robotic colposuspension using an alloplant is safe and can significantly improve quality of life indicators. The main advantages of this operation include the absence of allograft deformation and disease recurrence during patient examination as well as slighter injuries to the paraurethral tissues assisting the bladder in holding urine.